Enhancement of basal plane electrocatalytic hydrogen evolution activity via joint utilization of trivial and non-trivial surface states - Yang, Qun; Le, Congcong; Li, Guowei; Heine, Thomas; Felser, Claudia; Sun, Yan (Applied Materials Today, 2021)
Transition metal dichalcogenide semiconductors, particularly MoS2, are known as promising alternative non-precious hydrogen evolution reaction (HER) electrocatalysts to high-cost Pt. However, their performance is strongly limited by the poor conductivity and lack of active sites in the basal plane. Therefore, it is desirable to find alternatives with active basal plane sites or develop facile strategies to optimize the inert basal plane. In this work, we study the HER over topological semimetal Nb2S2C based on its basal plane. We report the first successful activation and optimization of the basal plane of Nb2S2C by synergistic using trivial surface states (SSs) and nontrivial topological surface states (TSSs). We find that the binding strength towards hydrogen adsorption of the easily cleaved sulfur(S)-terminated Nb2S2C surface can be stronger than that of 2H-MoS2, attributing to the presence of trivial SSs and nontrivial TSSs in Nb2S2C. By creating S vacancy on the basal plane, the binding strength towards hydrogen adsorption can be greatly optimized. The TSSs together with dangling-bonds reduce the Gibbs free energy to 0.31 eV, close to the peak of the volcano plot. This study provides a promising strategy for the joint utilization of the basal plane trivial SSs and TSSs for the HER.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dangling-bonds; Density functional theory; Gibbs free energy; Hydrogen evolution reaction; Topological semimetal; Topological surface states